2016
DOI: 10.1007/978-3-319-22533-3_23
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Thresholds and Doses of Intracranial Hypertension in Severe Traumatic Brain Injury

Abstract: Based on continuous monitoring of the pressure reactivity index (PRx), we defined individualized intracranial pressure (ICP) thresholds by graphing the relationship between ICP and PRx. We hypothesized that an "ICP dose" based on individually assessed ICP thresholds might correlate more closely with 6-month outcome compared with ICP doses derived from the recommended universal thresholds of 20 and 25 mmHg. Data from 327 patients with severe traumatic brain injury (TBI) were analyzed. ICP doses were computed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Previous publications employed manual direct observation of the relationship between PRx and ICP, via error bar plotting, to determine the individual ICP threshold. [4,5] It must be acknowledged that these individual thresholds for ICP do not represent therapeutic targets, but an individualized epidemiological thresholds, derived from the relationship between cerebrovascular reactivity values associated with global long-term outcome. Thus the derived individual thresholds quoted within the manuscript should not be considered as therapeutic in nature, and purely preliminary exploratory work into personalized ICP thresholds in TBI.…”
Section: Signal Acquisition and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications employed manual direct observation of the relationship between PRx and ICP, via error bar plotting, to determine the individual ICP threshold. [4,5] It must be acknowledged that these individual thresholds for ICP do not represent therapeutic targets, but an individualized epidemiological thresholds, derived from the relationship between cerebrovascular reactivity values associated with global long-term outcome. Thus the derived individual thresholds quoted within the manuscript should not be considered as therapeutic in nature, and purely preliminary exploratory work into personalized ICP thresholds in TBI.…”
Section: Signal Acquisition and Processingmentioning
confidence: 99%
“…[1][2][3] Aside from individualized CPP targets, individualized epidemiologic intracranial pressure (ICP) thresholds have been suggested based on a single center retrospective study in adult TBI. [4][5][6] Using the relationship between continuously monitored cerebrovascular reactivity, using the pressure reactivity index (PRx), and ICP, one can find the ICP threshold where all subsequent higher ICP values yield PRx measures consistently above +0.20, [4] a threshold value for PRx known to be associated with impaired cerebrovascular reactivity and global outcome in adult TBI. [7][8][9][10] This has been termed the patientspecific or individualized ICP threshold, identifiable in approximately 68% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…16 18 As we understand that ICP and CPP should be interpreted and tailored to patient's age, it is logical to assume that uptake of these techniques would optimize the individualization of TBI care. 27 28 Over the years, a dynamic protocol for monitoring CPP based on the autoregulatory capacity of the cerebral vascular system (pressure reactivity index [PRx]) has been proposed to determine optimal CPP (CPP opt ) for each patient. The PRx correlates well with Glasgow outcome scale 29 and is associated with improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate rose from 0% to 13% when ICP was above 40 mmHg, which was consistent with our animal experiment results. Some studies [35,36] suggested that the mortality rate begins to rise when ICP reaches 20–25 mmHg. Therefore, the target ICP set at 38 mmHg would be appropriate in the model, which not only caused brain injury, but ensured a low mortality rate.…”
Section: Discussionmentioning
confidence: 99%